Energy pricing economics and principles - Conkling, Roger L. 1917-; SpringerLink (Online service). (Berlin Heidelberg New York Springer, 2011)
This book describes the processes through which rates for energy consumption are derived, ranging from initial analyses of the supply and demand parameters to the final forms and levels of end-use consumer prices. The author argues against aggressive accounting procedures, and suggests criteria for choosing firm's position on pending public policy issues. A handbook on energy formulae for non-professionals is included in the book. The author is adjunct professor at the University of Portland.
Introduction -- The Cost Approach to Pricing: The Direction of Costs -- The Cost Approach to Pricing: Joint Cost Allocations -- The Cost Approach to Pricing: The Tenneco Pattern -- The Value Approach to Pricing: Demand Influence -- The Value Approach to Pricing: Planning for Demand -- The Public Policy/Social Engineering Approach to Pricing -- Introduction to Rates -- Elements to Rate Design -- Traditional Types of Rate Forms -- Tools of the Trade -- Matters of Judgment.
Electronic reproduction.
Keywords: Electric utilities -- Rates; Electronic books